Genomic Characterization of Lactobacillus delbrueckii Strains with Probiotics Properties - De Jesus, Luís Cláudio Lima; Aburjaile, Flávia Figueira; Sousa, Thiago De Jesus; Felice, Andrei Giacchetto; Soares, Siomar De Castro; Alcantara, Luiz Carlos Junior; Azevedo, Vasco Ariston De Carvalho (Frontiers in Bioinformatics, 2022)
Probiotics are health-beneficial microorganisms with mainly immunomodulatory and anti-inflammatory properties. Lactobacillus delbrueckii species is a common bacteria used in the dairy industry, and their benefits to hosting health have been reported. This study analyzed the core genome of nine strains of L. delbrueckii species with documented probiotics properties, focusing on genes related to their host health benefits. For this, a combined methodology including several software and databases (BPGA, SPAAN, BAGEL4, BioCyc, KEEG, and InterSPPI) was used to predict the most important characteristics related to L. delbrueckii strains probiose. Comparative genomics analyses revealed that L. delbrueckii probiotics strains shared essential genes related to acid and bile stress response and antimicrobial activity. Other standard features shared by these strains are surface layer proteins and extracellular proteins-encoding genes, with high adhesion profiles that interacted with human proteins of the inflammatory signaling pathways (TLR2/4-MAPK, TLR2/4-NF-κB, and NOD-like receptors). Among these, the PrtB serine protease appears to be a strong candidate responsible for the anti-inflammatory properties reported for these strains. Furthermore, genes with high proteolytic and metabolic activity capable of producing beneficial metabolites, such as acetate, bioactive peptides, and B-complex vitamins were also identified. These findings suggest that these proteins can be essential in biological mechanisms related to probiotics’ beneficial effects related to these strains in the host.